PENGARUH MEDIA PUZZLE TERHADAP KEMAMPUAN LOGIKA MATEMATIKA ANAK DI TAMAN KANAK-KANAK AISYIYAH BUSTANUL ATHFAL III CABANG KARUNRUNG KOTA MAKASSAR - Hasan, M.Pd, Dr. Herlina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
The aim of this research is, "To find out the description of mathematical logic abilities of group A children before and after in the form of Puzzle play activities in Aisyiyah Bustanul Athfal III Kindergarten Karunrung Branch and whether or not the influence of Puzzle play activities on the mathematical ability of Group A children in Kindergarten Aisyiyah Bustanul Athfal III Karunrung Branch. The approach used in this study is a quantitative approach to the type of Pre-Experimental research with One-Group Pretest-Posttest Design with a population of 13 research populations and does not determine the sample because of the small population. Data collection techniques carried out by observation and documentation techniques. Data collection procedures performed were planning, giving pretest, giving treatment, giving posttest and analyzing the results. The data analysis technique used is descriptive analysis and non-parametric statistical analysis using Wilcoxon different test analysis. The results showed that the value of children's mathematical logic abilities at the posttest and pretest were different. The results of hypothesis testing using the Wilcoxon different test showed that there was an effect of the activity of playing a puzzle on the ability of children's mathematical logic in kindergarten Aisyiyah Bustanul Athfal III Karunrung Group A